Outsourcing of Internal Audit Services in Australian Firms: Some Preliminary Evidence - Divesh S. Sharma; Nava Subramaniam (Asian Academy of Management Journal of Accounting and Finance, 2005)
Although internal auditing (IA) services have been traditionally performed in-house, organizations are increasingly outsourcing such services. Using a Transaction Cost Economics (TCE) perspective, this study examined the influence of several organizational-level variables on the decision to outsource or in-house their internal audit function. The study also identified the type of IA services that were likely to be out-sourced rather than in-housed, the extent to which incumbent external financial statement auditors participated in outsourced arrangements and the level of interaction between the internal audit provider and audit committees. The results have implications for auditor independence, corporate governance and organizational performance.